HR Development in The Mas Ubud Bali Tourism Village in Facing The Era of Tourism 4.0 - I Gusti Made Suka Arnawa; Nyoman Agus Trimandala; I Made Darsana (Institute of Computer Science (IOCS), 2022)
The change in tourism industry players and consumers moving towards digital is one of the phenomena that emerged in the tourism era 4.0. The Covid-19 pandemic has triggered an adjustment of business processes to this era. Reflecting on this, the tourist village of Mas Ubud Bali must adapt to tourism in the 4.0 era, adapting the capabilities of its human resources. From this review, the purpose of this study is to describe the development of human resources in the tourist village of Mas Ubud Bali in the face of the tourism era 4.0. This research is a descriptive qualitative research with data collection techniques through interviews. The results of the study conclude that the human resources of the tourist village of Mas Ubud Bali are ready to face the tourism era 4.0, because the human resources already have theoretical abilities, technical abilities, digital abilities, and personal abilities. However, of the four capabilities, there needs to be an increase in digital skills and personal abilities, because both are still not optimal. This research is expected to be a recommendation material for tourism village managers in compiling a relevant HR development model to be applied in the tourism 4.0 era.